An Empirical Comparison of Some Statistics for Identifying Outliers and Influential Observations in Linear Regression Models - Balasooriya, U. (Institutional Knowledge at Singapore Management University, 1987)
This paper reports the results of an empirical study of applying seven commonly used methods for identifying outliers and influential observations in linear regression models to six well-known data sets in the literature. The results show that the methods do not always agree. Observations which are detected as ‘significantly influential’ may only moderately affect the parameter estimates when they are removed from the regression. Combinations of procedures should be judiciously used in empirical studies.